Global, regional and local dimensions of western Saharás protracted decolonization : when a conflict gets old - Ojeda García, Raquel (Libros electrónicos en Ebscohost, 2017)
This book explores the traces of the passage of time on the protracted and intractable conflict of Western Sahara.